Partisipasi Suara Pemuda Dalam Sistem Politik Inonesia (Refleksi Pemilu 2024) - Helminasari, Shorea; Rahmiyati, Rahmiyati; Aladawiyah , Rabi’ah (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
The 2024 general election will be held on Wednesday, February 14, 2024, where youth participation in the 2024 election is indeed very significant and dominant. The role of youth is not only limited to being voters, but they are also actively involved in various aspects of election administration. The participation of youth votes in Indonesia's political system is a crucial aspect that reflects the dynamics of democracy and the regeneration of national leadership. This study aims to analyze the level of youth participation in the 2024 election, identify factors influencing their involvement, and evaluate the role of social media as a driver of political participation among the younger generation. The research method used is secondary data analysis from the official reports of the General Election Commission (KPU), case studies, and surveys related to young voters' behavior. The main findings show that youth participation, especially among Generation Z and millennials, has seen a significant increase compared to previous elections, driven by intensive digital campaigns and the use of social media as the primary source of political information. However, challenges such as misinformation and low digital literacy remain obstacles that need to be addressed. The conclusion of this study emphasizes the importance of strengthening political and digital literacy to ensure quality and sustainable youth participation in Indonesia's political system. This research provides an important contribution to understanding the dynamics of youth political participation and its implications for the future of Indonesian democracy.